Lessons learned from Vietnam's first COVID-19 vaccine rollout: tackling vaccine hesitancy and misinformation for future pandemic responses - Bui, Ngoc Minh Tam; Nguyen, Hong Trang; Duong, Bich Thuy; Susilawati, Tri Nugraha; Thai, Truc Thanh; Vu, Minh Thuy; Lin, Jialing; Bui, Thuy Anh; Duong, Minh Cuong (Frontiers in Public Health, 2025)
BackgroundVaccine hesitancy and misinformation significantly undermine pandemic preparedness. Insights from the COVID-19 vaccine rollout can inform and enhance future pandemic responses. During Vietnam's Delta outbreak in 2021, the vaccine rollout faced significant challenges including limited vaccine supply and public vaccine hesitancy, which impeded widespread coverage.ObjectivesThis study examined levels of COVID-19 vaccine hesitancy, common information sources, exposure to negative vaccine-related information, and intentions to promote vaccination among the Vietnamese public.MethodsA national cross-sectional survey was conducted in 2021 with 1,579 participants recruited through the snowball sampling method. Logistic regression analyses were used to identify factors associated with vaccine hesitancy.ResultsOverall, 30.6% of respondents were vaccine hesitators. Hesitancy was significantly higher among females [adjusted Odds Ratio (AOR) = 1.438, 95% CI: 1.132–1.892, P = 0.003), non-health students (AOR = 1.924, 95% CI: 1.017–3.642, P = 0.044), non-health workers (AOR = 2.168, 95% CI: 1.293–3.636, P = 0.003), those with a high school education (AOR = 2.073, 95% CI: 1.365–3.147, P = 0.001) or below (AOR = 2.722, 95% CI: 1.143–6.486, P = 0.024). Lower hesitancy was associated with prior paid vaccination (AOR = 0.718, 95% CI: 0.56–0.92, P = 0.009), and good vaccine knowledge (AOR = 0.484, 95% CI: 0.382–0.613, P < 0.001). Social media (76%), peers (65.9%), television news (63.6%), and newspapers (62.8%) were common information sources. Notably, 89% encountered negative or misleading information, and only 47.8% were willing to promote vaccination.ConclusionsAddressing vaccine hesitancy in future outbreaks of COVID-19 and other infectious diseases requires combating misinformation, especially on social media, and improving vaccine knowledge among lower-education groups. Individuals in health-related sectors and those who have previously paid for vaccinations can serve as role models in promoting vaccination. Clear, culturally appropriate communication and sustained government are vital to counter the infodemic, build trust, and improve vaccine uptake in future pandemics. Due to snowball sampling, the study findings may not generalize to rural, older, or less-educated populations. Future studies should consider stratified sampling to improve representativeness.